Spillovers and asset allocation - Lai Trung Hoang; Dirk G. Baur (Journal of Risk and Financial Management, 2021)
There is a large and growing literature on spillovers but no study that systematically evaluates the importance of spillovers for portfolio management. This paper provides such an analysis and demonstrates that spillovers are fully embedded in estimates of expected returns, variances, and correlations and that estimation of spillovers is not necessary for asset allocation. Simulations of typical empirical spillover settings further show that same-frequency spillovers are often negligible and spurious.
Keywords: C32; C58; G11; 330; asset allocation; portfolio optimization; return spillovers; spillover; volatility spillovers